The effect of porosity defects on the mid-cycle fatigue behavior of directed energy deposited Ti-6Al-4V. (June 2022) - Tang, Dingcheng; He, Xiaofan; Wu, Bin; Wang, Xiaobo; Wang, Tianshuai; Li, Yuhai
Highlights: Porosity-induced mid-cycle fatigue (MCF) behavior of directed energy deposited (DED) Ti-6Al-4V are investigated. Pore size classification method is quantitatively developed by combining microstructure and da/dN-Δ K curve in high vacuum. A quantitative study of the fine granular area (FGA) shows the Δ K FGA in the MCF regime is not a material constant. The stress level, pore size and pore-to-surface distance are important factors affecting fatigue behavior and performance. Abstract: This paper investigates the mid-cycle fatigue (MCF) behavior of as-built DED Ti-6Al-4V. Fatigue tests in groups at three stress levels were completed in a laboratory environment. The results show that internal pore initiation mode is more common for this material. The porosity-induced crack initiation mechanism involves a mixture of cleavage and intergranular fracture. Pore size classification method is quantitatively developed, which in turn elucidate the potential relationships among microstructure, pore size, fatigue behavior, and fatigue crack growth stages in high vacuum. A quantitative study of pore sizes and fine granular area (FGA) shows that the FGA stress intensity factor range Δ K FGA in the MCF regime is not a material constant. In addition, three key factors (i.e., stress level, pore size and pore-to-surface distance) affecting the fatigue behavior and performance of the material are discussed.